Hands-on machine learning for algorithmic trading : design and implement investment strategies based on smart algorithms that learn from data using Python - Jansen, Stefan (Packt Publishing, 2018)
With the help of this book, you'll build smart algorithmic models using machine learning algorithms covering tasks such as time series forecasting, backtesting, trade predictions, and more using easy-to-follow examples. By the end, you'll be able to adopt algorithmic trading in your own business and implement intelligent investigative strategies.